Eating habits and dental erosion among dental students at the University of San Gregorio de Portoviejo - López Castro, Kennie Saul (2025)
Introduction: Dietary habits include the repetitive consumption of acidic foods, carbonated beverages, and sour sweets, which can cause dental erosion, i.e., the loss of enamel due to intrinsic or extrinsic factors. The objective of this study was to determine dietary habits and dental erosion in students of the Dentistry Program at San Gregorio of Portoviejo University. Materials and methods: A descriptive, quantitative study was conducted. The sample consisted of dentistry students enrolled in the second to fifth semesters. The Basic Erosive Wear Examination was also used. This is a basic erosive wear examination that measures dental erosion based on a set of criteria and a scoring system. For this study, the procedure was based on clinical observation of the most affected teeth. Results: All participants presented some degree of dental erosion. Carbonated beverage consumption was found to be the most common dietary habit among dental students with dental erosion. The majority of those examined were characterized as having grade 2 dental erosion and a low risk level according of the method used. Conclusions: The dietary habits of dentistry students follow a consumption trend that begins with carbonated beverages, followed by citrus juices, acidic fruits, and sour sweets, which contribute to the progression of dental erosion, as evidenced by the clinical evaluation of the students.